1982
DOI: 10.1038/jcbfm.1982.31
|View full text |Cite
|
Sign up to set email alerts
|

A31P Nuclear Magnetic Resonancein vivoStudy of Cerebral Ischaemia in the Gerbil

Abstract: Summary:We have used the noninvasive method of "'phosphorus nuclear magnetic resonance C'P N MR) in \'il'O to follow changes in phosphorous me tabolite concentrations and the intracellular pH in the right and left hemi spheres and in the cerebellum of gerbil brains after the occlusion of the right carotid artery, Spatial resolution over the brain was possible using surface coils. Ligation, which is known to cause ischaemia in this species in the ipsilat eral hemisphere, resulted in the diminution of phosphocre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2

Year Published

1983
1983
1999
1999

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(29 citation statements)
references
References 16 publications
1
26
2
Order By: Relevance
“…The spectra from human infant brains differed from those found previously for animal brains (e.g. Ackerman et al 1980;Thulborn, Boulay, Duchen & Radda, 1982) in that the PCr peak was smaller and the most prominent peak in infant brain spectra, which was in the phosphomonoester (PME) region, was rather small and insignificant in the animal brain spectra. These differences could be related to species or to age.…”
Section: Introductioncontrasting
confidence: 48%
“…The spectra from human infant brains differed from those found previously for animal brains (e.g. Ackerman et al 1980;Thulborn, Boulay, Duchen & Radda, 1982) in that the PCr peak was smaller and the most prominent peak in infant brain spectra, which was in the phosphomonoester (PME) region, was rather small and insignificant in the animal brain spectra. These differences could be related to species or to age.…”
Section: Introductioncontrasting
confidence: 48%
“…The importance of CP as a relevant physiological parameter is stressed by the fact, that the CP concentration of brain decreases during hypoxia or seizures without significant changes in ATP-levels [35]. Only if in addition the blood flow is decreased, CP and ATP levels fall towards zero rather quickly [36]. These data indicate that regional and possibly also subcellular fluctuations of CP levels can occur in brain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, earlier NMR studies have shown a corre lation between abnormality of spectra and the pres ence of oedema in the gerbil brain (Thulborn et al, 1982). Again, it is probable that the water accumu lation is a consequence of the energy failure.…”
Section: Thresholdsmentioning
confidence: 96%